Genetic Testing for Inherited Cardiac Arrhythmias: Current State-of-the-Art and Future Avenues - Hylind, Robyn J. (J Innov Card Rhythm Manag, 2018)
The seminal discovery that sequence variation in genes encoding cardiac ion channels was behind the inherited cardiac arrhythmic syndromes has led to major advances in understanding the functional biological mechanisms of cardiomyocyte depolarization and repolarization. The cost and speed with which these genes can now be sequenced have allowed for genetic testing to become a major component of clinical care and have led to important ramifications, yet interpretation of specific variants needs to be performed within the context of the clinical findings in the proband and extended family. As technology continues to advance, the promise of therapeutic manipulation of certain genetic pathways grows ever more real.